Family-Owned Universities: Fit for the Twenty-First Century? - Choi, Edward; Altbach, Philip; de Wit, Hans; Allen, Matt (International Higher Education, 2021)
Family-Owned or -Managed Higher Education Institutions (FOMHEIs) are a remarkable phenomenon—which, despite having a global presence, is almost entirely ignored. FOMHEIs exist on every continent and number in the thousands. Many are established with a social mission and are nonprofit, while others are for-profit and linked to family businesses. Despite their unequivocal “familiness” dimension, FOMHEIs retain the character of academic enterprises, while departing from their nonfamily-based counterparts in several major ways.